2021
DOI: 10.1016/j.celrep.2021.109126
|View full text |Cite
|
Sign up to set email alerts
|

Systematic functional analysis of SARS-CoV-2 proteins uncovers viral innate immune antagonists and remaining vulnerabilities

Abstract: Highlights d Numerous SARS-CoV-2 proteins synergize to suppress immune sensing and signaling d Nsp14 targets IFNAR1 for lysosomal degradation d ORF3a and ORF7a block autophagy by different mechanisms d Synergistic treatment with IFN-g and -l1 is highly effective against SARS-CoV-2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
276
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(299 citation statements)
references
References 84 publications
15
276
2
6
Order By: Relevance
“…Other explanations for limited autophagy in SARS-CoV-2infected cells include recently described ORF3a, ORF7a, NSP15 involvement 65 , and particularly NSP1-dependent host protein translational shutoff 26,27 that might prevent the synthesis of autophagy-regulating proteins, maintain a high ATP/AMP ratio, and increase amino acid availability. The reduction of multiple Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations for limited autophagy in SARS-CoV-2infected cells include recently described ORF3a, ORF7a, NSP15 involvement 65 , and particularly NSP1-dependent host protein translational shutoff 26,27 that might prevent the synthesis of autophagy-regulating proteins, maintain a high ATP/AMP ratio, and increase amino acid availability. The reduction of multiple Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper [1], we showed that infection of human cells with SARS-CoV-2 reduces autophagic flux. This is characterized by two hallmarks, an accumulation of SQSTM1 and the increased presence of the processed form of LC3B, LC3B-II.…”
mentioning
confidence: 94%
“…One can envisage that escape of IFN-mediated restriction by betacoronaviruses is species-specific. For instance, SARS-CoV-2 Nsp14 targets human IFNAR1 for lysosomal degradation [62], but may be unable to degrade bat IFNAR1. This inability to evade IFN response in Eptesicus serotinus kidney cells and in Myotis myotis nasal epithelial cells may contribute to the cellular control of infection in FLG-ID and MmNep cells, as in experimentally infected Eptesicus fuscus [65].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 has evolved numerous synergetic mechanisms to evade the IFN response in human cells [62], resulting in an absence of IFN expression in some cells, including A549 cells [51,63]. The virus is unable to counteract ISG induction in Eptesicus serotinus kidney cells and in Myotis myotis nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%